Konsep Dasar Strategi pembelajaran (Direct Instruction) - Musriana Luthfiah Hasibuan; Nurmala Sari; Gusmaneli Gusmaneli (Concept: Journal of Social Humanities and Education, 2024)
In the learning process, strategy is a determining factor in the success ok learning. With this strategy, it is hoped that learning can achieve optimal results as desired. Based on data analysis, it can be concluded that the Islamic Religious Education learning strategy at SDN Loksado, Loksado District, Hulu Sungai Selatan Regency, can be said to have not been implemented well. This can be seen from the absence of strategies used by teachers in learning, and there are still factors that are less supportive, such as incomplete facilities, a school environment that is less supportive, and students' interest is still lacking.